Making Manila’s hottest a political economic analysis of Original Pilipino Music (OPM) programming at Monster RX93.1 - Maurillo, Carlo Salvador A.
This study explored how station operations influence the Original Pilipino Music (OPM) programming of Mega Manila FM radio station Monster RX93.1. With their continued relevance and wide reach, the music programming of FM stations like Monster serve as viable platforms for the wide promotion of local music and artists. However, this potential of radio can be hindered by factors related to the inner workings of each station. Using Jarl A. Ahlkvist’s programming philosophies and Jonathan Hardy’s critical political economy, the researcher entered inquiry assuming that radio in the Philippines is of a commercial orientation and thus had certain practices and inclinations towards music programming that were informed by key forces behind the scenes, such as ownership, programmers, and radio jocks, among others. The study found that Monster RX93.1’s nature as a niche station laid the foundation for heavy collaborative ideation, but final decisions for programming depended on the authority of the programmer. Anchored in its owners’ orientation towards innovation, the resulting philosophy for the station was a non-rational approach that prioritized station aesthetics and immersion in its upscale target audience, leading to a curated niche programming whose OPM offerings noteworthily provided platforms to both mainstream and independent Filipino artists. Monster RX93.1 sets an example for a vision towards programming that enriches art and culture amidst commercial interests.